2015
DOI: 10.3892/ijmm.2015.2301
|View full text |Cite
|
Sign up to set email alerts
|

N-trans-ρ-caffeoyl tyramine isolated from Tribulus terrestris exerts anti-inflammatory effects in lipopolysaccharide-stimulated RAW 264.7 cells

Abstract: Inflammation is induced by the expression of cyclooxygenase‑2 (COX‑2), which is an important mediator of chronic inflammatory diseases, such as rheumatoid arthritis, asthma and inflammatory bowel disease. Tribulus terrestris (T. terrestris) is known to have a beneficial effect on inflammatory diseases. In this study, we investigated the effects of N‑trans‑ρ‑caffeoyl tyramine (CT) isolated from T. terrestris on the production of nitric oxide (NO), and the expression of pro‑inflammatory cytokines and COX‑2 in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…This compound was tentatively identified as cannabisin B by comparison with the literature data (Sakakibara et al, ), and its molecular formula was reported as C 34 H 32 N 2 O 8 (Chen et al, ). Cannabisin B is highly regarded for its antioxidant activity as it inhibited arginase in in vitro assays (Bourjot et al, ) and exhibited anti‐inflammatory effects (Ko et al, ). Chen et al () provided evidence that hempseed hull, a by‐product that is usually discarded after the oil extraction process, could be used as a source of natural antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…This compound was tentatively identified as cannabisin B by comparison with the literature data (Sakakibara et al, ), and its molecular formula was reported as C 34 H 32 N 2 O 8 (Chen et al, ). Cannabisin B is highly regarded for its antioxidant activity as it inhibited arginase in in vitro assays (Bourjot et al, ) and exhibited anti‐inflammatory effects (Ko et al, ). Chen et al () provided evidence that hempseed hull, a by‐product that is usually discarded after the oil extraction process, could be used as a source of natural antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The eluent fractions G46-51-1-13 were obtained from this initial liquid chromatographic separation. The fractions were examined to an in vitro assay to assess their inhibitory effect on NO production ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…A constitutional isomer of the previous compound was N-caffeoyltyramine, which was found to inhibit macrophage-mediated inflammatory responses through the suppression of the production of NO and pro-inflammatory cytokines [31]. This compound was tentatively identified under peak 5.…”
Section: Hr-ms Analysis: Phenylamidesmentioning
confidence: 97%